HYBRID PWA NAVIGATION SYSTEM FOR COLLEGE CAMPUSES - Vibhandik, Nivedita; Kawale, Pranav; Sonar, Mayuresh; Divate, Mrunal; Sonar, Aditya (International Journal of Engineering Technologies and Management Research, 2025)
In our college we have seen that big campuses are often confusing to move around, specially for new students, visitors and also for people who are differently abled. Normal GPS apps are fine for outdoor navigation but they don’t really work when it comes to inside the buildings and complex routes of campus. So we started working on a Hybrid Progressive Web App (PWA) system, where we combine GPS for outdoor routes along with BLE beacons, WiFi, QR codes for indoor areas. While designing, we kept focus more on accessibility like adding voice assistance and wheelchair friendly paths, also on safety with emergency exits and campus security alerts. Another part we added was context aware navigation like giving option for less crowded paths, shaded areas or well lit routes. During our testing with students we saw that the accuracy indoor was close to 1–2 meters, also it saved time and users reported better satisfaction compared to only GPS based systems. From this we believe our approach can really be used in actual campus deployment.